2017
DOI: 10.1021/acs.cgd.7b01412
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Crystal Structure of dl-Arginine by Combined Powder X-ray Diffraction Data Analysis and Periodic DFT-D Calculations

Abstract: 2018. Elucidating the crystal structure of DL-Arginine by combined powder X-ray diffraction data analysis and periodic DFT-D calculations. AbstractAmong the 20 directly-encoded proteinogenic amino acids, arginine is one of five remaining cases for which the crystal structure of a racemic crystalline phase has not yet been reported. In this paper, the crystal structure of DL-arginine is determined by exploiting modern methods for analysis of powder X-ray diffraction data, in conjunction with periodic DFT-D calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Whereas X-Ray diffraction (XRD) is the established gold standard when single crystals are available, atomic-level structure determination is much more challenging in powder samples, and even more so if the structures are disordered. Indeed, while there has been much progress towards complete structure determination in crystalline powders, by powder XRD 1 , 2 or particularly from solid-state nuclear magnetic resonance (NMR) approaches 3 – 5 , the disorder inherent to amorphous solids makes structure determination elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas X-Ray diffraction (XRD) is the established gold standard when single crystals are available, atomic-level structure determination is much more challenging in powder samples, and even more so if the structures are disordered. Indeed, while there has been much progress towards complete structure determination in crystalline powders, by powder XRD 1 , 2 or particularly from solid-state nuclear magnetic resonance (NMR) approaches 3 – 5 , the disorder inherent to amorphous solids makes structure determination elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The observed peaks were correlated with the powder diffraction file no. 24–0734 (Joint Committee on Powder Diffraction Standards). , Pure l -Arg showed peaks at 11, 14.9, 16.9, 18.4, 19.1,19.5, 23.1, and 27.4° . After the surface modification of MNCs by Arg, the Arg@MNCs showed the peaks at 2θ values of 18, 28.9, 30.8, 36.1, 38.0, 44.4, 50.8, 53.9, 58.5, 59.9, and 64.6°.…”
Section: Resultsmentioning
confidence: 94%
“…39,40 Pure L-Arg showed peaks at 11, 14.9, 16.9, 18.4, 19.1,19.5, 23.1, and 27.4°. 45 After the surface modification of MNCs by Arg, the Arg@MNCs showed the peaks at 2θ values of 18, 28.9, 30.8, 36.1, 38.0, 44.4, 50.8, 53.9, 58.5, 59.9, and 64.6°. The observed results suggested that no other impurities have found in the phase purity measurements.…”
Section: Resultsmentioning
confidence: 95%
“…X-ray is a common means of material characterization that allows analysis of the crystalline structure and phase of a material [23][24][25]. As can be seen from Fig.…”
Section: Effect Of Preparation Methods On Characteristics Of Cuo/al 2mentioning
confidence: 99%